Alinhamento estratégico e coopetição : os efeitos no desempenho em cadeias de suprimentos da agroindústria de Mato Grosso - Sogabe, Vergilio Prado (2017)
The agribusiness is one of main economic activities in Brasil, representing approximately 22% of GDP in 2015 (MAPA, 2016). In Mato Grosso Estate, the agribusiness accounts for 50% of GDP and and soybean and maize crops account respectively for 9% and 2% of world production (IMEA, 2015; APROSOJA, 2016). Supply Chain Management represents the theoretical and empirical contribution that can allow a more agile strategic business management, able to respond to business opportunities, resulting from the coordination between the activities of production and distribution in an agroindustrial chain (BATALHA, SILVA, 2013; NEVES, 2015). In this way, this study proposes a managerial analysis based on supply chain approach and the influence of strategic alignment and coopetition over firms performance and the chains as a whole. For this, a research of mixed methods, of inductive character, was carried out. In the first phase of the research it was applied the qualitative method with a more exploratory bias. In - depth interviews were carried out, with the support of a semi - structured script, with the triad agents in the main producing regions of the state of MT. The interviews were recorded and intirely transcribed. The data were then analyzed according contents analysis techniques. With the support of the qualitative research, a closed questionnaire was developed to carry out the quantitative phase of the research. In the quantitative phase, a total of 157 valid questionnaires were collected, data after tabulations were analyzed according to the structural equations technique, PLS-PM, with the aid of SMARTPLS 2.0 software. The results of the two phases of the research suggest that companies share within their core activities the same competitive priorities, but there are some points of disagreement and fragility in the alignment of these factors. In the context of interorganizational relationship at CS level the coopetition management is performed in a less conscious way, because the agents are not familiar with the term. However, the agents perceive the existence of coopetitive tensions and the need for a balance of relationships through coopetition strategies. Finally, the statistical analysis allowed the estimation of a model that shows that there is an influence of the competitive priorities in the alignment of the chain and that this alignment has a positive and significant impact on the performance of companies and of the supply chain as a whole.